The effect of efficiency and inflation rate on the financial stability of banks in Asean-5 countries - Maudy, Maudy; Andriana, Isni; Mu’izzuddin, Mu’izzuddin; Widiyanti, Marlina (International research journal of management, IT and social sciences, 2024)
This study was conducted to examine and analyse the effect of efficiency and inflation rate on banking financial stability in ASEAN-5 countries from 2013 to 2023. The population in this study is all commercial banks in ASEAN-5 countries totalling 169. The sampling method used purposive sampling and obtained 133 banks that met the criteria so that they became samples in this study. The results of the panel data regression analysis in this study indicate that efficiency, as measured by the BOPO ratio, shows positive and significant results on banking financial stability as measured by z-score. However, efficiency measured by the BOPO ratio shows negative and significant results on stability measured by NPL. Inflation has a negative and significant effect on banking financial stability measured by z-score. Inflation has a negative and statistically insignificant effect on banking financial stability as measured by NPL.